Suppression of transcription factor PDX-1/IPF1/STF-1/IDX-1 causes no decrease in insulin mRNA in MIN6 cells. - Kajimoto, Y (1997)
The insulin gene transcription factor PDX-1/IPF1/STF-1/ IDX-1 plays a key role in directing beta cell-specific gene expressions. Recently, impairment of PDX-1 expression or activity has been observed in beta cell-derived HIT cells cultured under high glucose concentrations, and this has been suggested as a possible cause of the decrease in insulin gene transcription. To investigate the pathophysiological significance of PDX-1 as a determinant of the rate of insulin gene transcription, we suppressed its expression in beta cell-derived MIN6 cells using an antisense oligodeoxynucleotide (ODN) and searched for possible changes in the beta cell-specific gene expression. Treatment of MIN6 cells with an 18-mer phosphorothioate ODN complementary to a sequence starting at the translation initiation codon of PDX-1 caused a potent, concentration-dependent reduction in PDX-1 expression; addition of 2 microM antisense ODN could reduce PDX-1 expression to 14+/-4% of the control. There was also a decrease in its DNA binding to the insulin gene A element. Despite such suppression of PDX-1, Northern blot analysis revealed no decrease in the amount of insulin mRNA in the MIN6 cells. Similarly, no changes were detected in the transcription of the glucokinase or islet amyloid polypeptide gene, for which PDX-1 was shown to function as a transcription factor. Thus, our findings dispute the physiological significance of PDX-1 in determining the rate of insulin gene transcription. This means that other components constituting the transcription-controlling machinery need to be evaluated in order to understand the molecular basis of impaired insulin biosynthesis such as that observed due to glucose toxicity.